Orang Tua dan Pendidik Cerdas dalam Mengembangkan Kompetensi Sosial Anak Usia Dini - Syelindah, Yulia; Ismaniar, Ismaniar; Dasa Putri, Lili (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 1 (2024), 2024)
This article examines providing information for parents in developing social competence from an early age in order to have resilience skills. According to Salkin, children's social competence develops from birth and is influenced by their environment, especially parents and schools, as well as instilling human values ??in students such as morals, character and social solidarity and establishing oneself as a second person means understanding the soul and character of students. In the context of the educational process in schools, educators have the task of educating, teaching and training. This study was motivated by the large number of children who lack social skills such as temperament, self-image, and seeing other people's views. This study discusses how parents and educators shape and develop the social competence of early childhood. Based on the analysis in this paper, several tricks for being an intelligent parent and educator can be summarized in developing children's social competence related to social demands in accordance with social rules, values ??and expectations. Parents as the first madrasah for children are where children can develop their social potential and educators help academic success as well as build relationships with friends and a positive learning environment.